RETRACTED: Naskah Marba’ Fi Hukm An-Nikah Karya Syeikh ‘Abbas Al-Asyi (Tela’ah Ide Sentral) - Ruhamah Ruhamah; Amar Makruf (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This writing is about marba' script. The Marba’ Manuscript is one of the Fiqh manuscripts of many Acehnese manuscripts. This manuscript was originally a book written by Shaykh Abdul Mu'thi As-Samallawi of the Shafi'i school, which was later translated by Shaykh 'Abbas Al-'Asyi (Tgk.Chik Kuta Karang) in Malay which was also named after the name of the original book, namely Marba'. The Marba' Manuscript consists of several chapters and chapters, one of which is Al-Bab fi Hukm An-Nikah (chapter on stating all marriage laws) in the four schools of thought. Judging from its content, the Marba' manuscript contains fiqh knowledge which is very useful for the reader as a guide for the afterlife. This writing aims to find out the edited text of the manuscript Marba' fi Hukm An-Nikah Syeikh 'Abbas Al-'Asyi and the central idea of the manuscript Marba' fi Hukm An-Nikah Syeikh 'Abbas-Al-'Asyi.